1969
DOI: 10.1063/1.1652754
|View full text |Cite
|
Sign up to set email alerts
|

LARGE NONLINEAR OPTICAL COEFFICIENT AND PHASE MATCHED SECOND HARMONIC GENERATION IN LiIO3

Abstract: The second harmonic of a Nd laser has been produced in LiIO3 in a phase matching direction of 30° to the c axis with high conversion efficiency. The nonlinear optical coefficient t31 is among the highest so far reported for phase matchable substances using λ = 1.06 μ. LiIO3 can be grown from water solutions with excellent optical quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…For example, in a complex crystal A ? By using formula [1], we can write each item of the bond-valence equation of a complex crystal, and then the complex crystal is decomposed into forms that can be quantitatively calculated by means of the dielectric theory of solids (15)(16)(17).…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a complex crystal A ? By using formula [1], we can write each item of the bond-valence equation of a complex crystal, and then the complex crystal is decomposed into forms that can be quantitatively calculated by means of the dielectric theory of solids (15)(16)(17).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Single crystals of hexagonal lithium iodate ( -LiIO , space group P6 ) and orthorhombic hydrogen iodate (HIO , P2 2 2 ) have been of great interest for application in laser technology and in optoelectric devices, owing to their nonlinear optical properties (1)(2)(3). However, such applications require crystals of high quality and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Geusic et al [51] observed SHG at 532nm in Ba2NaNbO15 and KrLi4NbO3 using a lightly focused, continuously pumped, repetitively Q-switched Nd : YAG laser emitting light of wavelength 1.064/zm. Using ruby lasers (694.3 nm) and neodymium lasers (1.06/_tm), SHG was studied in some novel, strongly nonlinear materials, namely HIO3 [52] and Li[O3 [53]. Recently, Jerphagnon [54] corrected earlier values of the nonlinear susceptibilities of LiIO 3 by Maker's fringe technique [44] using a Nd 3 + : YAG laser with an acoustic Q-switching system.…”
Section: Shg In Transmitted Lightmentioning
confidence: 99%
“…The crystals used in second harmonic generation belong to the point group 6 and have a prismatic form, which is hexagonal in cross section. They are uni-axial and optically negative [5,6]. Various methods have been adopted by researchers [7 -11] to grow these crystals.…”
Section: Introductionmentioning
confidence: 99%
“…They have good nonlinear optical, electro-optical [3], photoelectric, and piezoelectric properties [4]. These crystals are of interest in second harmonic generation within the range 0.53 -1.06 µm [5]. The crystals used in second harmonic generation belong to the point group 6 and have a prismatic form, which is hexagonal in cross section.…”
Section: Introductionmentioning
confidence: 99%